A SURVEY ON OCCURRENCE OF HOUSE SPARROW (Passer domesticus) IN MADURAI DISTRICT, TAMILNADU, INDIA - MAXMELLION, P. MERLYNNA ESTHER; RENUKADEVI, K.; RAJENDRAN, PRIYATHARSINI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
House sparrow, well-known for its occurrence within the human surroundings was enlisted in IUCN Red Data List as least concern. The disappearance of this species was reported widely in India. Ornithologist Survey conducted by Indian Council of Agricultural Research (ICAR) reported that the sparrow population in Andhra Pradesh alone has dropped by 80% and in other states like Kerala, Gujarat and Rajasthan it has dipped by 20%, while the decline in coastal areas was as sharp as 70% to 80%. In order to assess the presence of this species in Madurai District, this study was designed and was conducted in a total of 168 places in which the sparrows were found in 109 places by line transect method. Interestingly the study revealed that there was 80% of occurrence of sparrow population found in urban and semi urban areas whereas 62% of occurrence in rural areas. This study revealed that house sparrows are not disappeared but still existing in Madurai District. Nesting sites was also recorded using Nikon p900 camera and it was found moderately in urban and semi urban areas. This may be due to the availability of nesting sites and food materials in such habitats. Fascinatingly in some rural areas the sparrows were not found. Hence it was concluded that there is some preference in the selection of habitat by the house sparrows.